2014
DOI: 10.1088/0960-1317/24/12/125007
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and modelling of injection moulded all-polymer capillary microvalves for passive microfluidic control

Abstract: Rapid prototyping is desirable when developing products. One example of such a product is all-polymer, passive flow controlled lab-on-a-chip systems that are preferential when developing low-cost disposable chips for point-of-care use. In this paper we investigate the following aspects of going from rapid prototyping to pilot (mass) production. (1) Fabrication of an all-polymer microfluidic system using a rapid prototyped master insert for injection moulding and ultrasonic welding, including a systematic exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The ultrasound energy makes the energy directors melt, allowing bonding of the two parts (Figure 1a,b). It was demonstrated that UW is a very useful tool for both self-aligned gapless welding of polymer chips and for sealing of low-aspect ratio, large-area microchannels [1,13,14,16,21,22]. Here, we focus on the use of UW for the integration of embedded metal electrodes in injection molded (IM) microfluidic chips (Figure 1b,c) made of cyclic olefin copolymer (COC).…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound energy makes the energy directors melt, allowing bonding of the two parts (Figure 1a,b). It was demonstrated that UW is a very useful tool for both self-aligned gapless welding of polymer chips and for sealing of low-aspect ratio, large-area microchannels [1,13,14,16,21,22]. Here, we focus on the use of UW for the integration of embedded metal electrodes in injection molded (IM) microfluidic chips (Figure 1b,c) made of cyclic olefin copolymer (COC).…”
Section: Introductionmentioning
confidence: 99%
“…Here we defined trigger valve success as when a valve holds liquid for at least 10 min without leakage. The success rate of trigger valves is highly related to their geometries . The geometric parameters known to affect the performance of capillary trigger valves are the height and width of the trigger valve, and the height difference between the TV and the release channel (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, they realized gas–water separation by simply constructing obstacle microstructures in the microchannels . Construction of hydrophobic obstacle microstructure in the microchannel increased the energy barrier for the flow of water, which could be explained by the Young–Laplace equation and the Gibbs inequality effect . Because of the large critical Laplace force in the outlet channel with microstructure, the water was guided into outlet channel without microstructure under a driving pressure of critical pressure, and gas flowed into another outlet channel (Figure B).…”
Section: Applicationsmentioning
confidence: 99%